A haemagglutination test for rapid detection of antibodies to SARS-CoV-2 - Townsend, A; Rijal, P; Xiao, J; Tan, TK; Schimanski, L; Rahikainen, R; Matthews, PC; Crook, D; Hoosdally, S; Dunachie, S; Barnes, E; Street, T; et al. (Springer Nature, 2021)
Serological detection of antibodies to SARS-CoV-2 is essential for establishing rates of seroconversion in populations, and for seeking evidence for a level of antibody that may be protective against COVID-19 disease. Several high-performance commercial tests have been described, but these require centralised laboratory facilities that are comparatively expensive, and therefore not available universally. Red cell agglutination tests do not require special equipment, are read by eye, have short development times, low cost and can be applied at the Point of Care. Here we describe a quantitative Haemagglutination test (HAT) for the detection of antibodies to the receptor binding domain of the SARS-CoV-2 spike protein. The HAT has a sensitivity of 90% and specificity of 99% for detection of antibodies after a PCR diagnosed infection. We will supply aliquots of the test reagent sufficient for ten thousand test wells free of charge to qualified research groups anywhere in the world.